Making solidarity effective. The interaction between Vietnamese diplomacy and solidarity activists in the mobilization for Vietnam in Belgium (1960s and early 1970s) - Christiaens, Kim (Die eine Welt schaffen : Praktiken von 'Internationaler Solidarität' und 'Internationaler Entwicklung' = Create One World : practices of 'International Solidarity' and 'International Development')
"Kim Christiaens"